Loop Swapping as a Potent Approach to Increase Ene Reductase Activity with Nicotinamide Adenine Dinucleotide (NADH) - Mähler, Christoph; Kratzl, Franziska; Vogel, Melina; Vinnenberg, Stefan; Weuster-Botz, Dirk; Castiglione, Kathrin (dvanced Synthesis & Catalysis, 2019)
The asymmetric reduction of alkenes is a widely used transformation in industry. Ene reductases (ERs) are (bα)8-barrel folded enzymes capable of catalyzing this hydrogenation reaction. At the expense of nicotinamide coenzymes, ERs can reduce a wide range of electron-deficient alkenes in an anti-specific manner and with high regio- and stereoselectivities. However, a cost-effective industrial use of these enzymes is hampered, since most ERs prefer Nicotinamide adenine dinucleotide phosphate (NADPH) to the more stable and less expensive non-phosphorylated Nicotinamide adenine dinucleotide (NADH) as coenzyme. Here, we demonstrate an approach to both modify the biocatalysts coenzyme selectivity and strongly increase the activity and affinity with NADH. By swapping loop regions of the cyanobacterial NostocER1 for the corresponding regions of two NADH-favoring ERs, a strong alteration of the biocatalyst's coenzyme binding was achieved. This made possible a transfer of the respective donor-ER kinetic parameters to NostocER1. Additionally, outperformance of both donors in terms of activity was achieved through combinatorial swapping of loops of both species. These findings demonstrate the high potential of loop swapping as protein engineering approach to selectively optimize the coenzyme binding of ERs.
Keywords: Biocatalysis; Protein engineering; Alkene reduction; Ene reductase; Cofactors; Loop swapping